Risk factors related to liver injury in non-Intensive Care Unit admitted patients infected with COVID-19: A retrospective study of 102 patients - Amir Sadeghi; Pegah Eslami; Arash Dooghaie Moghadam; Ali Pirsalehi; Sajad Shojaei; Laya Jalilian Khave; Ghazal Sanadgol; Taha Hasanzade; Dorsa Shirini; Hamid Asadzadeh Aghdaei; Saeed Abdi; Mohammad Reza Zali (Babol University of Medical Sciences, 2020)
Background: Liver is one of the target organs for COVID-19 infection. The liver damage in critically ill patients was investigated in previous studies, but there is no available data about liver injury in mild to moderate form of infection with COVID019. In this study, we estimated the prognostic factors related to liver injury in NON-ICU admitted patients infected with COVID-19. Methods: in this retrospective study, 102 eligible adult participants admitted in the ward were included. Demographic characteristics, admission duration, underlying disease, manifestations of infection, and laboratory data were analyzed. Then, with statistical, univariate, and multivariate analysis, the associated and independent factors were estimated. Results: the mean age of the study population was 55.13± 17.02 years old. The most common symptom was fever (45.8%). The most frequent co-morbidity was hypertension (25%). 65 patients had liver injury (63.72%). According to statistical analysis CRP were significantly higher in liver injury group (P=0.01, respectively). Univariate analysis reported ALKP, and CRP associated significantly with liver injury (P=0.04, OR= 1.003, Cl 95%= 1.000-1.007; P=0.03, OR= 1.009, Cl 95%= 1.000- 1.017, respectively). No independent factor was detected in multivariate analysis. Based on Spearman's rank correlation coefficients CRP and lymphocyte correlated significantly with AST (r=0.22, P=0.00; r=-0.13, P=0.09, respectively). Moreover, neutrophil, CRP, and lymphocyte correlated with ALT (r=0.27, P=0.01; r=0.23, P=0.02; r= -0.19, P=0.05, respectively). Conclusion: Although in the current study, no independent factor was detected, CRP had a significant association with liver injury. It appears the role of inflammatory pathways in the severity of this infection.